Gamification elements and their impacts on education: A review - Mao, Jun; Terry, Lucas (Malque Publishing, 2024)
Gamification, the integration of game design elements in non-gaming contexts, has emerged as a popular strategy across various disciplines, particularly in education. This meta-analysis evaluates the impact of gamification on student engagement, motivation, and academic performance from 2021 to 2024. A systematic review was conducted following PRISMA principles, analysing studies sourced from major academic databases, including ScienceDirect, Google Scholar, and Scopus. Peer-reviewed publications focusing on gamification elements such as badges, leaderboards, and points were prioritized. Findings indicate that gamification significantly enhances student motivation, active participation, and academic success. Specific features like badges and leaderboards foster competitiveness and recognition, which are essential for promoting self-regulation and active learning. Points systems, on the other hand, provide immediate feedback and measurable goals, enabling learners to track progress effectively. Collectively, these elements create dynamic, interactive, and enjoyable learning environments that facilitate deeper engagement and comprehension. This review also highlights the diversity of gamified approaches tailored to educational settings, demonstrating their adaptability to various subjects and age groups. The implementation of gamification has been shown to bridge gaps in traditional pedagogical methods by introducing novel ways of capturing student interest and sustaining long-term involvement. However, the effectiveness of gamification is contingent on careful design and alignment with instructional objectives. Overall, the findings underscore the transformative potential of gamification in education. By integrating game mechanics into learning processes, educators can cultivate intrinsically motivated learners and foster improved academic outcomes. The study concludes with recommendations for future research to explore the longitudinal effects of gamification and its applicability across diverse educational contexts.